Optimal Switching Sequence with a Specialized Tabu Search Algorithm - Puerta, Gabriel F. (2024)
This paper presents a tabu search algorithm designed to address the optimal switching sequence (OSS) problem within the context of the service restoration problem (SRP) in distribution systems. The OSS problem arises when a set of switches is supposed to be operated in order to reconfigure the system's topology from an initial state to a final state. When applied in the context of the SRP, the switches suggested to be operated will partially or fully restore the disconnected loads. In this context, the main challenge is to obtain an optimal switching sequence where the energy not supplied during the entire restoration process is minimal and all the intermediate topologies are feasible. The algorithm was tested using a 53-node distribution system, and the results for the two different scenarios showed the algorithm's effectiveness in elaborating a feasible switching sequence that significantly reduces the cost of energy not supplied.